Light House Chacachacaree [sic], Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
Picture of a lighthouse located at Chacachacare, an island off the north west coast of Trinidad. There is a flag post, a tank and a single story house located close to the lighthouse.
Colour: Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Lighthouses--Trinidad and Tobago; Islands--Trinidad and Tobago; Chacachacare